Attention economics of Instagram stars: #instafame and sex sells? - Sophia Gänßle (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
Social media stars create stardom with uploads on social media pages like YouTube, TikTok or Instagram. One of the most popular platforms, especially designed to upload picture contents, is the service "Instagram" owned by Facebook. The growing social, cultural and economic power of social media star phenomenon raises the question about key drivers of success. Does body exposure drive Instagram success? Is there a difference between male and female content in this regard? This paper empirically analyses 500 top Instagram stars within the categories (1) fashion and beauty, (2) fitness and sports, (3) music, (4) photo and arts, (5) food and vegan. The unbalanced panel data set consists of 100 stars within each category over an observation period of five months. The data provides information on popularity measurements, such as subscribers, likes and comments, and most importantly, price estimates per post. Since influencers are not paid by the platform, but mainly by advertisers for promotion of their products, the estimated price per upload combined with the posting frequency serve as a valid proxy for weekly revenue and economic success. Mean comparison tests show that accounts with focus on female accounts have a significantly higher degree in body exposure, while the price per picture is higher for male content. Weekly revenues do not significantly diverge. Furthermore, using panel regressions, I estimate the effect of body exposure and sex on advertising revenue. The results show that body exposure has a positive effect, whereas the sex has no significant influence in the regression estimations. Eventually, this raises the question of a gender pay gap in social media.
Keywords: 330; cultural and creative industries; attention economics; superstar theory; social media stars; influencers; Instagram; gender pay gap